School Indiscipline Post-Covid-19 Pandemic in Ceará Education - Souza, Gabriela Pereira (2022)
This work aims to present, from the perspective of the teacher, the factors that contribute to school indiscipline in the return of face-to-face school activities after the post-Covid-19 pandemic social isolation. It is pertinent that indiscipline in the classroom is a complicating factor for teaching and learning to occur, and that remote teaching has mischaracterized the idea of ​​the formal classroom, group participation, and other activities of school praxis in the learning context. . The research was carried out through electronic questionnaires, with teachers from the state public network of Ceará. The main challenge for teachers, in the current context of education, is to develop students' socio-emotional skills, motivating themselves and redoing their pedagogical work.